Prevalence, Characteristics, and Associated Risk Factors of Wrist Fractures in Americans Above 50: The Cross-Sectional NHANES Study - Ye, Juncai; Li, Qiao; Nie, Jing (Frontiers in Endocrinology, 2022)
Summary By analyzing data from NHANES, we aimed to evaluate the prevalence, characteristics, and associated factors of wrist fractures in Americans aged 50 and above. Introduction Wrist fractures, whose prevalence increases with age, are one of the most common fractures in the United States. However, epidemiological studies on the prevalence of wrist fractures of certain ages were limited. Methods The data of Americans aged 50 or above from 2013–2014 and 2017–2018 in NHANES were extracted and analyzed. Results The prevalence of wrist fractures among Americans whose age was 50 or above was 12%, which was similar between men and women (men 12.8% vs. women 11.4%, p = 0.267). Among those who had experienced their first wrist fracture, 17.8% of the population experienced a second wrist fracture. The top two causes of the first wrist fracture were a fall from a standing height (56%) or a hard fall (34.8%). The prevalence of wrist fractures was higher in men than in women (13.7% versus 8.7%, p = 0.023) aged < 60, but higher in women than in men aged ≥ 60 (11.8% versus 14.3%, p = 0.007). Multivariate analysis showed that obesity, frequent drinking, current smoking, high serum phosphate level, non-Hispanic white women, and osteoporosis were independently associated with wrist fractures. Stratified by race, osteoporosis, frequent drinking, and high serum phosphate level were risk factors for wrist fractures in all races. As for Mexican Americans, non-Hispanic whites, and other races including multi-racial, current smoking was a risk factor of wrist factures. Furthermore, obesity was positively associated with wrist fractures in Mexican Americans, other Hispanics, and non-Hispanic whites. Conclusion The prevalence of wrist fractures in Americans aged 50 and above was 12%. Falling from a standing height was the main cause of the first wrist fracture. Frequent drinking, current smoker, high serum phosphate level, osteoporosis, obesity, and non-Hispanic women were more likely to experience wrist fractures.